Memory-efficient boundary-preserving tetrahedralization of large three-dimensional meshes - Erkoç, Ziya; Güdükbay, Uğur; Si, Hang (Engineering with computers, 2024)
We propose a divide-and-conquer algorithm to tetrahedralize three-dimensional meshes in a boundary-preserving fashion. It consists of three stages: Input Partitioning , Surface Closure , and Merge . We first partition the input into several pieces to reduce the problem size. We apply 2D Triangulation to close the open boundaries to make new pieces watertight. Each piece is then sent to TetGen , a Delaunay-based tetrahedral mesh generator tool that forms the basis for our implementation. We finally merge each tetrahedral mesh to calculate the final solution. In addition, we apply post-processing to remove the vertices we introduced during the input partitioning stage to preserve the input triangles. The benefit of our approach is that it can reduce peak memory usage or increase the speed of the process. It can even tetrahedralize meshes that TetGen cannot do due to the peak memory requirement. Graphical abstract